PERANAN SALES FORCE EFFECTIVENESS DAN PROSES UPLOAD DATA MASTER LIST CUSTOMER KE DALAM SYSTEM PADA PT TAKEDA INDONESIA - Harjoko, Harjoko; Fandalita, Sherly (JAB (Jurnal Akuntansi & Bisnis), 2020)
This research was conducted to determine the role of Sales Force Effectiveness and the process of uploading customer master list data into the system at PT Takeda Indonesia, how to find obstacles and alternative solutions in problem solving. Data collection techniques through literature study and observation, namely by directly observing the object under study. Based on the results of the discussion, it shows that the role of Sales Force Effectiveness in a company aims to assist the sales team in making effective sales through customer data management. The process of uploading customer master list data into the system is in accordance with the existing data upload process standards in the company.The obstacles faced by the sales force effectiveness in carrying out its role include the lack of adequate facilities, lack of thoroughness, and inadequate communication. Obstacles during the process of uploading customer master list data into the system include the occurrence of double codes, inappropriate names, delays in providing data, inappropriate data formats, errors in the system and slow internet network. Solutions that can be done in dealing with obstacles in the role of Sales Force Effectiveness include replacing computer devices and internet networks with better specifications, conducting training, and making systems that are connected between divisions. Solutions taken in facing obstacles during the process of uploading customer master list data into the system include validating data, reminding the sales team to send data before maturity, providing examples of data formats, the IT team should ensure that the system on each computer does not occur errors. and the internet network used is good.Â Keywords: Sales Force Effectiveness, Master List, Customer